Aplicabilidade do ácido hialurônico como coadjuvante ao tratamento periodontal não cirúrgico: uma revisão de literatura. - GARCIA, Beatriz dos Reis Nabarrete (2021)
The present work aims to present a literature review, which aims to present an analysis regarding the applicability of hyaluronic acid as an adjunct to non-surgical periodontal treatment, and this review was elaborated from research in academic articles in the field of Periodontics, hosted in databases such as Scholar Google, PubMed and SciELO. Based on the analyzed studies, it was possible to observe that in all cases of application of hyaluronic acid as an adjunct to non-surgical periodontal treatment, apparently positive results were obtained, however, it was concluded that more studies are needed to confirm the reliability of these results.